Konsep Manusia Dalam Pandangan Svami Vivekananda: Sebuah Kajian Antropologi Metafisik - Siswadi, Gede Agus; Puspadewi, I Dewa Ayu (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Man, on the one hand, is understood as a creation on earth, like all earthly things, and on the other hand, a man appears on earth and seeks to reach a higher life. Higher life here is a level of life that has a higher quality in a more transcendental sense compared to everyday life in this world. Humans can thus be understood in essence or human existence along with the activities and characteristics attached to it. So that in this context there are various mentions for humans because they have complex natures. But it is also necessary to explore human reality based on the ontological elements of the human being to answer the question of whether humans are formed from one element, two, or even plural. So this study aims to explore ontologically human nature from the view of Svami Vivekananda. This study uses a qualitative method with a philosophical hermeneutic approach. The results of this study indicate that Vivekananda views humans as essentially the same as Brahman, in the sense that humans are existentially different from Brahman but are essentially the same as Brahman. Vivekananda describes the body as the name of a series of changes. This is understandable because the body is always changing and is composed of changing particles. The real man is the soul, not the body. This explanation also seems to be a form of direct rejection of materialism. And man has the divine nature of God.